2016
DOI: 10.1364/oe.24.023450
|View full text |Cite
|
Sign up to set email alerts
|

All-fiber mode-locked laser via short single-wall carbon nanotubes interacting with evanescent wave in photonic crystal fiber

Abstract: We report an all-fiber passively mode-locked laser based on a saturable absorber fabricated by filling short single-wall carbon nanotubes into cladding holes of grapefruit-type photonic crystal fiber. The single-wall carbon nanotube is insensitive to polarization of light for its one-dimensional structure, which suppresses the polarization dependence loss. Carbon nanotubes interact with photonic crystal fiber with ultra-weak evanescent field, which enhances the damage threshold of the saturable absorber and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…This results in unstable laser radiation parameters and eventual degradation of the polymer [8,9]. In order to circumvent this problem, various methods were proposed, which allow direct deposition of CNT onto optical surfaces through which laser radiation passes [10][11][12][13] or upon which it is reflected [14]. These methods, however, are relatively complicated.…”
Section: Introductionmentioning
confidence: 99%
“…This results in unstable laser radiation parameters and eventual degradation of the polymer [8,9]. In order to circumvent this problem, various methods were proposed, which allow direct deposition of CNT onto optical surfaces through which laser radiation passes [10][11][12][13] or upon which it is reflected [14]. These methods, however, are relatively complicated.…”
Section: Introductionmentioning
confidence: 99%
“…4) Hollow-core fiber: Another evanescent field interaction was presented by filling short SWCNT, graphene nanoparticle, and graphene/polyvinyl acetate (PVAc) into hollow-core fiber and hollow-core photonic crystal fiber (PCF), which is expected to increase the light-material interaction length, α s and damage threshold. [59,239,240] The PCF fiber structure is sketched as depicted in Figure 11d. The PCF-SA structure could work for high-power laser operation even with pump power up to 7 W. [241] The PVAc maintains the original morphology of the graphene sheet, which is easily deformed on optical deposition thus preserving the intact optical nonlinearity of graphene.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%
“…The most popular type of SWNT SA used in fiber lasers concentrates on polymer composite film, which is mechanically or optically sandwiched between fiber connectors. Another approach based on the evanescent field can be a candidate, and SWNTs can be coated on a D-shaped fiber [ 122 ], microfiber [ 184 ], or injected into micro slots [ 185 , 186 ], photonic crystal fiber [ 187 ], and hollow-core optical fiber (HOF) [ 188 ]. Choi et al demonstrated the nonlinear interaction scheme of SWCNTs with laser light by using the HOF, which offers the advantages of robust, efficient, and long interaction of guided light with SWCNTs with a simple fabrication process (inset of Figure 7 a) [ 188 ].…”
Section: Ultrafast Fiber Laser Based On Ld Samentioning
confidence: 99%